2018
DOI: 10.1111/cas.13736
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of aprepitant in Japanese patients treated with cisplatin‐containing highly emetogenic chemotherapy

Abstract: Chemotherapy‐induced nausea and vomiting (CINV) remains a major adverse event in cancer chemotherapy. Although aprepitant is effective in preventing CINV, an increment in financial burden for uniform use of aprepitant is a concern. The aim of the present study was to define the cost‐effectiveness of aprepitant from the perspective of the Japanese National Health Insurance system. Based on the results of a randomized phase II trial comparing an aprepitant‐containing regimen versus a nonaprepitant regimen in Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Although cisplatin is the most commonly used antineoplastic drugs in the treatment of many patients with solid organ cancer, it has strong side effects on the gastrointestinal tract [49]. As reported previously, cisplatin at a dose of 6 mg/ kg induced pica within 8 hours after administration of the drug, and these behaviors continued for 5 days [35].…”
Section: Discussionsupporting
confidence: 58%
“…Although cisplatin is the most commonly used antineoplastic drugs in the treatment of many patients with solid organ cancer, it has strong side effects on the gastrointestinal tract [49]. As reported previously, cisplatin at a dose of 6 mg/ kg induced pica within 8 hours after administration of the drug, and these behaviors continued for 5 days [35].…”
Section: Discussionsupporting
confidence: 58%
“…Kashiwa et al reported the cost-effectiveness of palonosetron in cisplatin-containing HEC regimens based on the TRIPLE study results conducted in Japan [13,21] [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, we simulated model patients treated with highly emetogenic cisplatincontaining chemotherapy and developed a decision-analytic model (Fig. 1) [12][13][14][15][16]. Based on a phase III clinical trial conducted in Japan (J-FORCE study) [7], the model patients received either a four-drug or a three-drug regimen.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al report a QoL evaluation using a visual analog scale according to the presence or absence of CINV by chemotherapy [20]. Including this report, according to previous CINV reports [13, 14, 21, 22], utility values were applied to the three health states. The following utility values were defined: 0.9 for CP with no significant nausea or vomiting; 0.2 for IR with nausea and vomiting; and 0.7 for CRB without vomiting or use of rescue medication.…”
Section: Methodsmentioning
confidence: 99%